Hydrogen Sulfide Epigenetically Mitigates Bone Loss through OPG/RANKL Regulation During Hyperhomocysteinemia in Mice - Behera, Jyotirmaya (Bone, 2018)
Hydrogen sulfide (H(2)S) is a novel gasotransmitter produced endogenously in mammalian cells, which works by mediating diverse physiological functions. An imbalance in H(2)S metabolism is associated with defective bone homeostasis. However, it is unknown whether H(2)S plays any epigenetic role in bone loss induced by hyperhomocysteinemia (HHcy). We demonstrate that diet-induced HHcy, a mouse model of metabolite induced osteoporosis, alters homocysteine metabolism by decreasing plasma levels of H(2)S. Treatment with NaHS (H(2)S donor), normalizes the plasma level of H(2)S and further alleviates HHcy induced trabecular bone loss and mechanical strength. Mechanistic studies have shown that DNMT1 expression is higher in the HHcy condition. The data show that activated phospho-JNK binds to the DNMT1 promoter and causes epigenetic DNA hyper-methylation of the OPG gene. This leads to activation of RANKL expression and mediates osteoclastogenesis. However, administration of NaHS could prevent HHcy induced bone loss. Therefore, H(2)S could be used as a novel therapy for HHcy mediated bone loss.